Determinant Factors of Firm Value: Cash Holdings and Dividend Policy as Mediation - Eka Yudhyani; Umi Kulsum; Faizal Reza; Astrid Napita Sitorus; Nanda Wahyu Indah Kirana (JASF: Journal of Accounting and Strategic Finance, 2022)
In times of uncertainty such as a crisis, a company needs to maintain its value for its investors. Theory suggests that for uncertainty, the company needs to have cash holding, but on the other hand, it needs to pay dividends. Therefore, this research aims to prove the relationship between factors that affect firm value with cash holding and dividend policy as mediation. We conduct this research on the manufacturing company from 2015 to 2021 registered on Indonesia Stock Exchange. Using the purposive sampling method, 82 company was chosen and 574 data was studied. To test our hypotheses, we use SmartPLS. The results proved that cash holding can influence firm value, while dividend policy cannot. For the indirect effect, we found that profitability and net working capital indirectly affect firm value through cash holding. We explain the theory and practical implications and describe our study’s limitations. For future research, we suggest differentiating firm value before and during a financial crisis, and the industry sector that has the worst, moderate, and light impact from the crisis.